Peer effects, personal characteristics and asset allocation - Zhang, Annie C.; Fang, Jiali; Jacobsen, Ben; Marshall, Ben R. (Journal of Banking & Finance, 2018)
We study the relative importance of social factors (including household, workplace, and neighborhood peer effects) and personal characteristics (including age, gender, tax rates, and funds under management) for asset allocation decisions. The most important factors (in order) are household peer effects, personal characteristics and workplace peer effects. Neighborhood peer effects and financial advice play a less important role. We use instrumental variables for both household and workplace peer effects and find results that are consistent with causal peer effects.